Design, Development, and Testing of a Device for Gene Electrotransfer to Skin Cells In Vivo - Aleksandra Cvetkoska; Janja Dermol-Černe; Damijan Miklavčič; Simona Kranjc Brezar; Boštjan Markelc; Gregor Serša; Matej Reberšek (MDPI AG, 2022)
Gene electrotransfer (GET) is considered one of the most efficient, safe, reproducible, and cost-effective methods of gene therapy, in which a gene is delivered to the cells in the form of a plasmid DNA vector by a method known as electroporation. To achieve successful electroporation, cells must be exposed to sufficiently high electric fields generated by short-duration, high-voltage electrical pulses that result in a temporary increase in plasma membrane permeability. The electrical pulses are generated by pulse generators (electroporators) and delivered to the cells via electrodes (applicators). However, there is a lack of standardized pulse delivery protocols as well as certified clinical pulse generators and applicators for gene delivery. In this paper, the development of a new pulse generator, applicator, and pulse delivery protocol for GET to skin cells is presented. A numerical model of electroporated skin developed and tested for two electrode configurations and two different pulse delivery protocols is also presented. An alternative pulse delivery protocol was proposed. The developed pulse generator, applicator, and the proposed pulse delivery protocol were then used in vivo for GET to skin cells in mice. The results showed high efficiency of the proposed pulse delivery protocol for the purpose of GET in mouse skin cells. Specifically, electroporation with the developed pulse generator, applicator, and proposed pulse delivery protocol resulted in higher gene expression in skin cells compared to the currently used pulse generator, applicator, and pulse delivery protocol.